PENATALAKSANAAN FISIOTERAPI PADA KASUS HNP DENGAN MODALITAS SHORTWAVE DIATERMY,TRAKSI LUMBAL DAN MC. KENZIE EXERCISE DI RSUD. Prof. Dr. MARGONO SOEKARJO PURWOKERTO - Dwi Susilo Ady Nugroho; Andung Maheswara (Pena Jurnal Ilmu Pengetahuan Dan Teknologi, 2013)
In  patients  with  HNP  (Hernia  Nucleus  Pulposus)  will  usually  arise  low  back  pain  that radiates  to  the  lower  leg  area  even  up  to  the  end  of  the  toes  and  also  characterized  by severe  pain  when  the  patient  straining  or  sneezing.  Given  the  pain,  then  there  will  be muscle  spasm  around  the  vertebrae  and  limited  motion  in  the  lumbar  spine  (flexion, extension,).  Issues  arising  from  this,  will  affect  the  activities  of  daily  life  can’t  work according to their field and can’t enjoy leisure time due to pain breaks. For effective and efficient  handling  performed  an  inspection  method  nyri  with  VDS  (Visual  Descriptive Scale),  muscle  strength  checks  MMT  (Manual  Muscle  Testing)  examination  joints  with limitation  of  motion  of  LGS  (Mid  line)  Examination  of  the  functional  activity  Owestry scale. As for the goal to be achieved in reducing muscle spasm pain and, increase muscle strength, increase range of motion, and improve the patient's functional activities for daily life - today. Most patients will improve HNP in 6 weeks with conservative therapy. Small proportion will develop into chronic despite terapeutik, in patients in surgery 90% will be improved,  especially leg pain,  but the likelihood of recurrence  is 50% and can  be at  the same level or different discs.Key Word : HNP, Intervensi SWD, Traksi Lumbal,  and Mc. Kenzie exercise.